Skeletal materials from the yard of St. Leonard church at Lubiń (vojvodeship Leszno, Western Poland) dated at 13-th - 18-th century - Henneberg, Maciej; Wrzesińska, Anna; Brodnicka, Jolanta (Anthropological Review, 1984)
Village of Lubiń is a site of Benedictine monastery since 11th century. St. Leonard church was built at the turn of 12th and 13th century as a parochial church serving local population (conventual church belonging to the monastic complex was constructed in 11th century but apparently served other purposes). Territory around St. Leonard church was used as a cemetery since 13th century until 1813. Usage was very intensive, so that graves were dug at the same places several times (up to 10 times). This practice resulted in a number of incomplete, partially damaged skeletons encountered during excavation conducted during 1979 - 1980. Trenches were placed all around the church, covering about 40% of the whole area of the cemetery. In the excavated area 662 primary internments and two large (several cubic meters each) ossuaries were encountered. It may be estimated that the total number of deceased primarily or secondarily interned at the cemetery amounted to 5-10 thousand individuals. On grounds of position of each skeleton in relation to others, stratigraphy, and scanty grave goods the whole series of skeletal materials was subdivided into four chronological samples: 13th - 14th c. 13th - 16th c. 17th c. and 18th — beginning of 19th c. (see tables 1, 3. 5). Dating is not very precise and may result in obscuring some microevolutionary or secular trends. From among the whole sample of skeletons originating from primary interments only about 180 were complete enough to warrant craniometric and osteometric analysis tsee tables 2 and 4 for exact numbers). These were only adult skeletons. Comparison of chronological samples by means of analysis of variance did not reveal any significant time trends, except brachycephalisation and its necessary correlates. Therefore detailed data are presented for the pooled sample. Majority of the diameters were measured in a standard way and labelled accordingly in tables 2 and 4 (numbers denoting characters correspond to those given by Martin and Saller [1957]). Last two rows in table 2 are cranial capacity (reconstructed by Manouvrier's formula) and cranial module (sum of length, breadth and ba-b). last two rows in table 4 present stature (Trotter and Glesser tables) and body weight (Gralla et al. 1974 method), Circumferences (see „obwód..." in table 4) of long bones were measured in an unorthodox way to give better idea about their robusticity. Namely circumference of a shaft of humerus was measured at tuberositas deltoidea, of tibia at distal end of linea poplitea and circumferences of other bones at foramen nutricium. Male crania from chronological subsamples were compared between themselves dy means of Mahalanobis’ D2 distance. Only the earliest (13th - 14th c.) sample shows statistically significant distances from others. This may be due to its very smal size and effects of brachycephalization. Series from St. Leonard church is similar to the series from the conventual church of the monastery (see „krypta” in table 5), though the distance is significant. Comparison of thc two series from Lubiń (male crania to other cranial samples of similar dating shows (table 6), that morphological similarity decreases smoothly with geographical distance (correlation between statisticai distance D2 and geographical distance d is quite high — 07-0.8 — and highly significant — see formulas in the text). On these grounds it may be concluded that people buried at Lubiń constituted a part of continuous population of Poland. and more loosely — of Europe, the were not a selected group. However, their average stature is high for their times. This may indicate positive influence exerted by the monastery upon environmental conditions under wii local people developed - medical and social care, better nutrition through higher level of agriculture etc.